Free Volume, Molecular Mobility and Polymer Structure: Towards the Rational Design of Multi-Functional Materials - Enrione, J (Polish Academy of Sciences, 2014)
In this short paper we illustrate the versatility of positron annihilation lifetime spectrometry when used for material characterisation by presenting a selection of recent lifetime studies carried out on novel polymeric materials with a wide range of potential industrial applications. We highlight the importance of local free volume in governing the macroscopic properties (e.g. permeation properties, mechanical strength) of these materials and how lifetime measurements can be used in conjunction with a number of complementary techniques in order to establish composition-structure-property relationships for these systems.